2013
DOI: 10.1177/1088767913511459
|View full text |Cite
|
Sign up to set email alerts
|

Animal Abuse as a Warning Sign of School Massacres

Abstract: Although animal cruelty is often described as a warning sign of future human violence, particularly in the prediction of multiple homicides, prior studies reveal mixed support for this notion and lack conceptual clarity in the measurement of such cruelty. This study investigates the quantity and quality of cruelty present in a sample of 23 perpetrators of school massacres from 1988 to 2012. Findings indicate that 43% of the perpetrators commit animal cruelty before schoolyard massacres and that the cruelty is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
2
21
0
2
Order By: Relevance
“…As we prepared this article, the USA experienced another horrific school shooting that took place in Parkland, FL (“At least 17 dead in Florida school shooting, law enforcement says”, https://www.cnn.com/2018/02/14/us/florida-high-school-shooting/index.html). Reviews of the AA backgrounds of school shooters rarely include officially documented reports of such behavior; most often rely on media coverage and anecdotal statements of peers (Arluke & Madfis, ). It is almost pro forma to assume that mass and serial killers have a history of AA.…”
Section: Aa and Crimementioning
confidence: 99%
See 1 more Smart Citation
“…As we prepared this article, the USA experienced another horrific school shooting that took place in Parkland, FL (“At least 17 dead in Florida school shooting, law enforcement says”, https://www.cnn.com/2018/02/14/us/florida-high-school-shooting/index.html). Reviews of the AA backgrounds of school shooters rarely include officially documented reports of such behavior; most often rely on media coverage and anecdotal statements of peers (Arluke & Madfis, ). It is almost pro forma to assume that mass and serial killers have a history of AA.…”
Section: Aa and Crimementioning
confidence: 99%
“…It is almost pro forma to assume that mass and serial killers have a history of AA. However, Arluke and Madfis () reported that, among 23 perpetrators of school shootings between 1998 and 2012, the majority (57%) had no history of AA. Indeed, a recent meta‐analysis (Patterson‐Kane, ) of studies examining AA among violent offenders noted a relatively weak link between AA and human‐directed violence, as the majority of those who mistreat animals do not go on to perpetrate violent acts against humans.…”
Section: Aa and Crimementioning
confidence: 99%
“…The literature concerning mass and serial murderers has also found a connection between childhood animal cruelty and later interpersonal violence, again noting the potential red flags for such early behaviors (Arluke & Madfis, ; Ressler, Burgess, Hartman, Douglas, & McCormack, ; Verlinden, ; Wright & Hensley, ). Additionally, other studies have found such a link by using prison populations to ascertain whether or not inmates in those institutions who retrospectively reported committing childhood animal abuse went on to engage in violence against humans (Hensley, Tallichet, & Dutkiewicz, ; Merz‐Perez & Heide, ; Merz‐Perez, Heide, & Silverman, ; Tallichet & Hensley, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has already been supported that there is a positive relation between animal cruelty and violence (from homicide to family violence) [33] [34] [35] [36] [37]. Dominant hypotheses on this issue are that overflowing aggressiveness or hatred against human beings is supposed to occur on animals or that the same violence which is directed against human beings of society in general, is also directed against animals.…”
Section: Introductionmentioning
confidence: 99%